ANALISIS KELAYAKAN FINANSIAL USAHATANI JAGUNG PIPIL (Zea mays L.) (Studi Kasus: Desa Ciherang Kecamatan Nagreg Kabupaten Bandung) - Pratiwi, Nabila Dian; Abubakar, Abubakar; Afifah, Lutfi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Corn is one of the important agricultural commodities for the community. Corn has benefits, namely for food, feed, fuel and industrial raw materials. Animal feed made from shelled corn is a promising potential. One area that develops shelled corn is Bandung Regency. Most of the farmers have not carried out input and output calculations to determine the profit and feasibility of the farming being carried out. This study aims to analyze farming costs, acceptance, income and feasibility of shelled corn farming in Ciherang Village, Nagreg District, Bandung Regency. The research area was determined purposively (intentionally). The sampling method uses non-probability sampling with accidental sampling techniques. In this study using primary data and secondary data. Primary data collection used interview techniques with questionnaires and secondary data obtained from the Central Bureau of Statistics, Bandung District Agriculture Office and Ciherang Village Office. The results showed that the average production cost of shelled corn farming for one growing season was IDR 7,399,636/ha. The average income earned by farmers is IDR 32,130,000/ha. The income earned by shelled corn farmers in one planting season is IDR 24,730,364/ha. Based on the analysis of the value of the R/C Ratio, it is known that the R/C Ratio value of shelled corn farmers in Ciherang Village is 4.3, which means that every one rupiah spent will generate 4.3 rupiah in revenue, so is shelled corn farming feasible because the value of R/C > 1. Flat corn farmers in Ciherang Village will break even if the farmers are able to sell 175.88 kg of shelled corn at a selling price of IDR 1,174/kg and produce a revenue BEP of IDR 887,795.